Expression of the Ebola Virus VP24 Protein Compromises the Integrity of the Nuclear Envelope and Induces a Laminopathy-Like Cellular Phenotype - Santiago Vidal; Maite Sánchez-Aparicio; Rocío Seoane; Ahmed El Motiam; Emily V. Nelson; Yanis H. Bouzaher; Maite Baz-Martínez; Isabel García-Dorival; Susana Gonzalo; Enrique Vázquez; Anxo Vidal; César Muñoz-Fontela; et al. (mBio, 2021)
ABSTRACT Ebola virus (EBOV) VP24 protein is a nucleocapsid-associated protein that inhibits interferon (IFN) gene expression and counteracts the IFN-mediated antiviral response, preventing nuclear import of signal transducer and activator of transcription 1 (STAT1). Proteomic studies to identify additional EBOV VP24 partners have pointed to the nuclear membrane component emerin as a potential element of the VP24 cellular interactome. Here, we have further studied this interaction and its impact on cell biology. We demonstrate that VP24 interacts with emerin but also with other components of the inner nuclear membrane, such as lamin A/C and lamin B. We also show that VP24 diminishes the interaction between emerin and lamin A/C and compromises the integrity of the nuclear membrane. This disruption is associated with nuclear morphological abnormalities, activation of a DNA damage response, the phosphorylation of extracellular signal-regulated kinase (ERK), and the induction of interferon-stimulated gene 15 (ISG15). Interestingly, expression of VP24 also promoted the cytoplasmic translocation and downmodulation of barrier-to-autointegration factor (BAF), a common interactor of lamin A/C and emerin, leading to repression of the BAF-regulated CSF1 gene. Importantly, we found that EBOV infection results in the activation of pathways associated with nuclear envelope damage, consistent with our observations in cells expressing VP24. In summary, here we demonstrate that VP24 acts at the nuclear membrane, causing morphological and functional changes in cells that recapitulate several of the hallmarks of laminopathy diseases. IMPORTANCE The Ebola virus (EBOV) VP24 protein is a nucleocapsid-associated protein with multiple functions. Proteomic studies have identified the cellular nuclear membrane component emerin as a potential VP24 interactor. Here, we demonstrate that VP24 not only interacts with emerin but also with lamin A/C and lamin B, prompting nuclear membrane disruption. This disruption is associated with nuclear morphological abnormalities, activation of a DNA damage response, the phosphorylation of extracellular signal-regulated kinase (ERK), and the induction of interferon-stimulated gene 15 (ISG15). Interestingly, VP24 also promotes the cytoplasmic translocation and downmodulation of barrier-to-autointegration factor (BAF), leading to repression of the BAF-regulated CSF1 gene. Finally, we show that EBOV infection also results in the activation of pathways associated with nuclear envelope damage, consistent with our observations in cells expressing VP24. These results reveal novel activities of EBOV VP24 protein, resulting in a cell phenotype similar to that of most laminopathies, with potential impact on EBOV replication.